The Role of Spinal Cord Compression in Predicting Intraoperative Neurophysiological Monitoring Events in Patients With Kyphotic Deformity: A Magnetic Resonance Imaging-Based Study - Zhen Jin; Jie Li; Hui Xu; Zongshan Hu; Yanjie Xu; Ziyang Tang; Yong Qiu; Zhen Liu; Zezhang Zhu (Neurospine, 2024)
Objective To establish a novel classification system for predicting the risk of intraoperative neurophysiological monitoring (IONM) events in surgically-treated patients with kyphotic deformity. Methods Patients with kyphotic deformity who underwent surgical correction of cervicothoracic, thoracic, or thoracolumbar kyphosis in our center from July 2005 to December 2020 were recruited. We proposed a classification system to describe the morphology of the spinal cord on T2-weighted sagittal magnetic resonance imaging: type A, circular/symmetric cord with visible cerebrospinal fluid (CSF) between the cord and vertebral body; type B, circular/oval/symmetric cord with no visible CSF between the cord and vertebral body; type C, spinal cord that is fattened/deformed by the vertebral body, with no visible CSF between the cord and vertebral body. Furthermore, based on type C, the spinal cord compression ratio (CR) < 50% was defined as the subtype C-, while the spinal cord CR ≥ 50% was defined as the subtype C+. IONM event was documented, and a comparative analysis was made to evaluate the prevalence of IONM events among patients with diverse spinal cord types. Results A total of 294 patients were reviewed, including 73 in type A; 153 in type B; 53 in subtype C- and 15 in subtype C+. Lower extremity transcranial motor-evoked potentials and/or somatosensory evoked potentials were lost intraoperatively in 41 cases (13.9%), among which 4 patients with type C showed no return of spinal cord monitoring data. The 14 subtype C+ patients (93.3%) had IONM events. Univariate logistic regression analysis showed that patients with a type C spinal cord (subtype C-: odds ratio [OR], 10.390; 95% confidence interval [CI], 2.215–48.735; p = 0.003; subtype C+, OR, 497.000; 95% CI, 42.126– 5,863.611; p < 0.001) are at significantly higher risk of a positive IONM event during deformity correction compared to those with a type A. In further multiple logistic regression analysis, the spinal cord classification (OR, 5.371; 95% CI, 2.966–9.727; p < 0.001) was confirmed as an independent risk factor for IONM events. Conclusion We presented a new spinal cord classification system based on the relative position of the spinal cord and vertebrae to predict the risk of IONM events in patients with kyphotic deformity. In patients with type C spinal cord, especially those in C+ cases, it is essential to be aware of potential IONM events, and adopt standard operating procedures to facilitate neurological recovery.